Hydatid Disease in the Turkana District of Kenya. III. The Significance of Wild Animals in the Transmission of Echinococcus granulosus, with Particular Reference to Turkana and Masailand in Kenya - Macpherson, C. N. L.; Karstad, L.; French, C. M.; Stevenson, P.; Arundel, J. H. (Pathogens and Global Health - Annals of Tropical Medicine and Parasitology, 1983)
The results are given of a study on the role of wildlife in the transmission of Echinococcus granulosus in the Turkana and Narok Districts of Kenya. A total of 76 wild carnivores belonging to three separate species was examined from Turkana District. Echinococcus adults were found in 11 of 38 silver-backed jackals (Canis mesomelas) and in six of 22 golden jackals (Canis aureus). This is the first record of golden jackals being infected with this parasite in Kenya. None of 16 spotted hyaenas (Crocuta crocuta) harboured the parasite. Morphological features of the parasites obtained from the jackals were compared with material obtained from dogs in the same area. No morphological differences were recorded when this material was compared with data reported by others, hence the Turkana material belonged to the single species E. granulosus. Three silver-backed jackals and three puppies (Canis familiaris) were successfully infected with protoscolices obtained from a hydatid cyst surgically removed from a Turkana patient. Three spotted hyaenas fed the same material failed to become infected. None of 152 wild herbivores of five species examined in Turkana harboured hydatid cysts. The natural jackal infections in this District are thought to be incidental and dependent on the continuance of the domestic cycle. The role of the Turkana themselves in the perpetuation of the cycle is discussed. Twenty-six wild herbivores of six species were examined for hydatid cysts, in Narok District; hydatids were found in three wildebeest (Connochaetes taurinus) and a single topi (Damaliscus korrigum). The discovery of fertile cysts in wildebeest and the reported infections in lions (Panthera leo), Cape hunting dogs (Lycaon pictus) and silver-backed jackals, support previous evidence of the existence of a wildlife cycle in the Masailand and Serengeti regions of East Africa. The relationship of this cycle to the domestic cycle operating in the same area is unclear and requires further investigation.
Keywords: Turkana; Narok; Silver-backed jackals (Canis mesomelas); Golden jackals (Canis aureus); Spotted hyaenas (Crocuta crocuta); Hydatid; Wildebeest; Lions (Panthera leo); Cape hunting dogs (Lycaon pictus); Masailand; Serengeti